The Role of Interpersonal Communication of Educators for Students with Special Needs at Tat Wam Asi Special School in Baubau - St. Nurazizah Mallarangeng; Hastuti Hastuti; Muh. Hidayatullah (Penerbit Jurnal Indonesia, 2024)
The aim of this research is to understand the role of interpersonal communication between educators and special needs students, as well as to identify the supporting and inhibiting factors in implementing interpersonal communication at SLB Tat Twam Asi. The method used in this research is a qualitative method. Data collection was carried out through three methods: observation, interviews, and documentation. The data analysis was conducted through data reduction, data display, and conclusion drawing.The results of the research indicate that the role of interpersonal communication between educators and students at SLB Tat Twam Asi significantly influences various aspects within the school, especially in the learning domain. Interpersonal communication affects learning activities, play, and all interactions of students at school. It serves as a bridging tool between educators and students in their interactions. Without well-established interpersonal communication, the learning process becomes difficult to conduct. Personal approaches by educators to students help create a comfortable and enjoyable learning environment. The supporting factors include school facilities and the close relationship between educators and students. The inhibiting factors are the lack of classrooms and educators, lack of parental support, and the mental disorders experienced by the students.